ANALISIS MANAJEMEN PERPUSTAKAAN BERDASARKAN PERATURAN NO. 24 TAHUN 2007 OLEH MENTERI PENDIDIKAN NASIONAL (Studi Kasus di MAN Pekalongan) - Tria Ratnasari; Dian Nur Muniroh (Institut Agama Islam Syubbanul Wathon Magelang, 2023)
Today the development of the era makes the world of education vying to improve quality. One way is to carry out good management and improvement in the context of fulfilling the facilities and infrastructure. As well as supporting facilities and infrastructure in the educational institution. For this reason, the government through Regulation of the Minister of National Education No. 24 of 2007 sets the standard for infrastructure in an educational institution. With this regulation, the government hopes that every school will be able to manage and provide facilities and infrastructure in accordance with the guidelines listed. This is like the management of school facilities and infrastructure in the library.This research uses descriptive qualitative research with source analysis through data collected by observation, interviews and documentation. Then the available data is processed by reduction, presentation and conclusion techniques and the results are that the Implementation of Library Management at MAN Pekalongan is guided by the Regulation of the Minister of National Education No. 24 of 2007. The stages are planning, procurement, regulation, use, deletion and structuring. In the procurement process, the process is closely related to the Permendiknas, because the procurement is oriented to the ratio and type guidelines contained in the regulation. Because this is evidence that the management carried out by the library has actually been carried out in accordance with the rules, both from the government or the general rules of the school.